Training kit (Exam 70-462) : administering Microsoft SQL Server® 2012 databases - Thomas, Orin (Microsoft Press WashingtonUS, 2012)
Relates to the technologies in SQL Server 2012. Presents information on installing and configuring SQL Server 2012; managing instances and databases; optimising and troubleshooting, and managing SQL Server 2012 data.